The role of novelty and fat and sugar concentration in food selection by captive tufted capuchins (Sapajus apella). Issue 8 (2nd July 2020) - Heuberger, Benjamin; Paukner, Annika; Wooddell, Lauren J.; Kasman, Matt; Hammond, Ross A.
Abstract: Capuchins, like other primates, use feedback from sensory cues and digestion to make decisions about which foods to consume and which to avoid. However, little is known about how capuchins make consumption decisions when simultaneously presented with novel and familiar foods, or how food familiarity and macronutrient concentration together influence food choice, topics with potential implications for developmental and health research. In this study, we evaluated the role of familiarity, as well as fat and sugar concentration, in the food selections of captive tufted capuchins ( Sapajus apella ). In the first experiment, over 10 sessions, subjects were assigned to either a group that chose between one familiar and one novel food item both high in fat or sugar (high condition), or to a group that chose between one familiar and one novel food item both low in fat or sugar (low condition). In the second experiment, subjects were divided into three groups, familiarized with food over five feeding sessions, and then offered the familiarized food and a novel food that varied in fat or sugar for 10 sessions. When offered foods high in fat, capuchins showed no clear signs of neophobia, forming an initial preference for the novel food, rejecting foods less frequently, and selecting foods faster than when offered foods low in fat. These trends were generally not observed in response to foods with sugar. When presented with options that varied in macronutrient concentration, subjects showed an initial interest in the novel food irrespective of whether it was high in fat or sugar, yet formed a final preference for the higher‐concentration item. Findings suggest that the concentration of fat or sugar in novel foods may be an important mediator of exploratory behavior and that capuchins rely on immediate feedback from taste and other sensory cues to make consumption decisions. Abstract : Capuchins in the high fat group were more likely to consume the novel food than capuchins in the low fat group in both the initial phase and final phase. They were also less likely to consume the familiar food than the low condition group in both the initial phase and final phase. Research Highlights: Capuchins showed neophilic responses toward a choice between a novel and familiar food when the foods are high in fat, but not when they are low in fat or sugar. When presented with a novel and familiar food that differed in fat or sugar content, capuchins selected the food higher in fat or sugar more often, yet showed initial interest in the novel food regardless of its fat or sugar content.